2009
DOI: 10.1021/ja802741b
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and Hydrogen Spillover of Bridged Metal-Organic Frameworks

Abstract: The metal-organic frameworks (MOF) with low and medium specific surface areas (SSA) were shown to be able to adsorb hydrogen via bridged spillover at room temperature (RT) up to an amount of full coverage of hydrogen in the MOF. Anomalous small-angle X-ray scattering was employed to investigate the key relationship between the structures and storage properties of the involved materials. It was found that the tunable imperfect lattice defects and the 3D pore network in the MOF crystal are the most critical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 31 publications
12
80
0
1
Order By: Relevance
“…Based on this ratio, Pt/AC/CB/IRMOF-8 prepared here has the same enhancement factors as that observed by Yang et al [6]. Our previous study showed that the adsorption kinetics via hydrogen spillover slowed with increasing pressure [19]. For the modified HPTGA measurement achieved by extending the measurement time to reach equilibrium, the slope of the isotherm (hydrogen uptake vs. pressure) increases, providing an additional margin of enhancement.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Based on this ratio, Pt/AC/CB/IRMOF-8 prepared here has the same enhancement factors as that observed by Yang et al [6]. Our previous study showed that the adsorption kinetics via hydrogen spillover slowed with increasing pressure [19]. For the modified HPTGA measurement achieved by extending the measurement time to reach equilibrium, the slope of the isotherm (hydrogen uptake vs. pressure) increases, providing an additional margin of enhancement.…”
Section: Resultssupporting
confidence: 77%
“…By comparison, the conventional measurement required several hours to over 1 day to complete. Additionally, it is important to point out that our bridged samples have very slow adsorption kinetics due to the diffusion limit of atomic hydrogen at RT [19]. In the present study, equilibrium of adsorption was achieved by extending the HPTGA measurement for up to 72 h at each pressure increment in the isotherm curve.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although a powerful tool for structural analysis [14,[21][22][23][24], SAXS has one inherent limitation, namely its inability to extract small particle location. This precludes obtaining a detailed understanding of the correlation between the particle geometry and the spatial distribution of impregnated Pt in the supporting material.…”
Section: Introductionmentioning
confidence: 99%